1983
DOI: 10.1080/03601238309372371
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hazards associated with pesticide container disposal and of rinsing procedures as a means of enabling disposal of pesticide containers in sanitary landfills

Abstract: To study problems associated with pesticide container disposal, a small vegetable production area in southwestern Ontario, the Thedford Marsh, was selected as the site for a model study. A container collection system was organized during the 1981 growing season, with collections being made from the ca. 50 growers on the marsh twice each month. In addition to the regular collection program a cleanup service for empty pesticide containers stored on farms or discarded on public lands also was initiated. More than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
(1 reference statement)
0
4
0
Order By: Relevance
“…Use of suitable solvents (e.g. acetone; Remler, 1923) combined with a rinsing procedure (Miles et al, 1983) could provide a suitable means to remove residues. We note that such procedures have two key weaknesses (1) manual operations of this nature (see section 2.3) are onerous and time-consuming and do not offer a viable prospect at scale, and (2) waste products in the form of a mixture of acetone, water and nail varnish are generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of suitable solvents (e.g. acetone; Remler, 1923) combined with a rinsing procedure (Miles et al, 1983) could provide a suitable means to remove residues. We note that such procedures have two key weaknesses (1) manual operations of this nature (see section 2.3) are onerous and time-consuming and do not offer a viable prospect at scale, and (2) waste products in the form of a mixture of acetone, water and nail varnish are generated.…”
Section: Discussionmentioning
confidence: 99%
“…A modified triple rinse procedure, originally used to clean pesticide containers, was utilized to remove residues of nail varnish from nail varnish packaging. This method was selected as it is an accepted, widely used cleaning method and it is suitable for glass and plastic containers used for nail varnish (Miles et al, 1983). All work had to be carried out within a fume cupboard due to the presence of volatile substances within the nail varnish residues.…”
Section: Packaging and Nail Varnish Residuesmentioning
confidence: 99%
“…As regards the triple-rinsing procedure, in 1983 Miles et al assessed it along with problems associated with pesticide container disposal, in a small vegetable-production area in southwestern Ontario (Miles, Harris, and Morrow 1983). A container-collection system was organized, with collections being made from growers twice each month.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Lamberton et al (4) stated that a simple rinsing with clear water can remove most pesticides from their containers. Miles et al (6) reported that triple rinsing with water left less than 0.1% of the original content in the container. Wesley et al (13) indicated that no visible 2,4-D injury on cotton (Gossypium hirsutum L.) was detected after spraying with the washing water from the third and fourth rinsing cycles of a pesticide mixing system.…”
Section: Introductionmentioning
confidence: 99%